ENDOMETRIAL POLYP WITH ENDOMETRIAL HYPERPLASIA &CHRONIC INFLAMMATION IN RABBITS - Asmaa Sh.Aliawy (Basrah Journal of Veterinary Research)
Rabbits were treated with large does of progesterone for up to 420 days developed numerous cysts of the endometrial ,sometimes associated with atypical .Histological of examination was performed on uterine biopsy samples of irregular cystic (polyp) masses noted .During caesarean section of a 2 month –old female Rabbits ,Microscopically examination revealed dilated hyperplasia gland with focal back to tack appearance ,surrounded by spindle ,fibrocystic-like cells ,stroma, heavy plasma cells infiltration of the endometrial by widely scattered viable and degenerate neutrophils ,lymphocytes , and plasma cells admixed with mild amounts of cellular debris and hemorrhage. The endometrial was markedly expanded by many irregular polyps and hyperplasic gland .Grossly one uterus was slightly thickened with pale mucous membranes .Where as the other uterus had numerous small ,4 mm in diameter, translucent cysts diffusely scattered on the endometrial surface .2x1.5x1 cm polyp oval ,hard, gray-blue smooth surface. Shows pink and bluish thin with small cysts.